Design of Web-Based Badminton Court Reservation System for Graha Pancasila Pandeglang Using Laravel Framework - Adi Winata; Umar Mansyuri; Rahadian Arief (Brilliance: Research of Artificial Intelligence, 2025)
The manual reservation system at Badminton Graha Pancasila Pandeglang often led to inefficiencies, including overlapping bookings, data recording errors, and difficulties in tracking payment history. These issues created the need for a structured, digital solution to manage reservations, user data, and transactions more effectively. This research aims to design and develop a web-based badminton court rental system that streamlines the booking process while enhancing accuracy and user convenience. The system was built using the Laravel framework and MySQL as its database, following the Waterfall development model. Black-box testing was used to validate all system functionalities. The core features include user registration with email verification, login, real-time court booking, cart and checkout process, digital payment integration using Midtrans, and booking history tracking. An admin dashboard was also implemented to monitor transactions, booking data, and user management. The testing results show that each feature works according to its functional requirements, with all tested cases returning successful results. The implementation of this system significantly improves operational efficiency, transparency, and user experience compared to the previous manual process. However, some limitations remain, such as the lack of real-time notifications and mobile optimization, which are recommended for future development. Overall, the system meets the research objectives and demonstrates the benefits of applying digital solutions to local sports facility management